Pengembangan Kognitif Bentuk Geometri pada Anak - Drajat Stiawan; Amilatu Dzakiroh (UIN Raden Mas Said Surakarta, 2021)
One of the children's developments that is quite important to note is the child's cognitive development. The purpose of this study was to find out how to implement the cognitive development of geometric shapes and to know what are the advantages and disadvantages of implementing the cognitive development of geometric shapes in group B at TKM Permata Hati, Rowoyoso Village, Wonokerto Pekalongan. This research method uses a qualitative approach with the type of field research. Data collection techniques using observation, interviews and documentation. Type of analysis used is the Miles and Huberman model, namely, data collection, data reduction process, data presentation process, conclusion and verification. The results showed that the implementation carried out with playing blocks, playing puzzles and playing the geometry creation board could develop children's cognitive abilities in recognizing geometric shapes in group B at Permata Hati TKM. There are 2 children who have difficulty recognizing geometric shapes, but there are 3 children who have been able to develop their cognitive abilities.